Identifikasi Mycobacterium Tuberculosis pada Pengobatan Pasien Rawat Jalan dengan Keluhan Batuk Persisten di Klinik Yudisman Cimahi - Anisa Insani Rahesti Kurnia; Rida Emelia (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium Tuberculosis and is still a significant global health challenge, especially in Indonesia which ranks second in the world in terms of Tuberculosis (TB) caseload. Cimahi city, as a densely populated urban area, has high risk of transmission due to limited population mobility and air quality. The main clinical symptom that is often ignored is a persistent cough for two weeks or more, which should be an importants indicator for immediate laboratory identification to pevent further transmission. This study aims to identify the presence of Mycobacterium Tuberculosis in outpatients with complaints of persistent cough at the Yudisman Cimahi Clinic and evaluate the effectiveness of treatment. The research method used was retrospective descriptive by analyzing the medical record of 30 patients in the period March-June 2025 who has completed 6 months of treatment. The results showed that Tuberculosis (TB) infection was dominated by men (56,7%) and the productive adult age group 26-45 years (46,7%). The high number in this group is associated with lifestyle factors such as smoking and the intensity of air contact in public spaces. The diagnosis is made using a dual method, namely the Rapid Molecular Test (TCM) which has high sensitivity in detecting bacterial DNA fragments, as well as microscopic examination of acid-fast bacteria (BTA) to confirm the patient’s potential for transmission. All research samples received pharmacotherapy intervention using fixed doses of Anti-Tuberculosis Drugs (OAT) through two phases of treatment, namely an intensive phase for 2 months and a continuation phase for 4 months. The final results of the treatment showed an excellent success rate with 70% of oatients desclared “Cure” and 30% of patients declared “Complete Treatment”. This success proves rhe effectiveness and vital role of Drug Ingestion Monitors (PMO) in preventing the occurrence of drug resistance or MDR-TB.